Dynamique des régulations en classe virtuelle ou en présentiel - Carrupt, Romaine; Barras, Hervé (e-JIREF, 2019)
The purpose of this exploratory research is to determine the contributions and limitations of a formative assessment in a virtual classroom in a hybrid professional teacher education system. Hybrid teaching refers to a combination of distance and face-to-face teaching modalities supported by digital technologies. The regulation of learning is defined as a set of adjustments and control operations aiming at a learning progression for the student. We hypothesize that the type of teaching device influences the regulations produced by the students. We recorded the speeches produced by eight students during a peer-review task in virtual and faceto- face classrooms. The productions are evaluated according to their level of regulation. The results show that interactive regulations differ according to the mediated context in favour of a high level of regulation in the virtual classroom. We also note that in face-to-face class, students reconfigure the prescribed task. The students' activities thus seem to be differentiated according to the modality and the conditions in which the task takes place. The conclusions drawn from the analysis of this exploratory use enrich the didactic reflection on tasks and social forms of work in virtual classrooms.
Keywords: Classe virtuelle; formation hybride; régulation des apprentissages; régulation interactive